LECTINOCHEMICAL CHARACTERISTICS OF THE GLANDULAR ZONE OF THE HARD PALATINE MUCOSA IN RATS AFTER THE EFFECT OF 1% METHACRYLIC ACID ETHER - G.A. Yeroshenko; Y.V. Tymoshenko; K.V. Shevchenko; O.D. Lysachenko; N.A. Ulanovska-Tsyba (Проблеми екології та медицини)
Decreased secretory activity of the salivary glands leads to deterioration of the general condition and aggravation of dental diseases in patients, which determines the relevance of the chosen topic. We identified changes in the morpho-functional state of the mucous membrane of the hard palate under the conditions of experimental hyposalivation by the method of lectin probing. This method is significantly superior to traditional methods of histochemical verification of carbohydrates due to its sensitivity and selectivity for the detection of these molecular structures. HPA lectin was used to identify the expression of carbohydrate determinants in the structural elements of the glandular zone of the mucous membrane of the hard palate in rats.